Computing for adults : an essential guide for beginers. - Clarke, Alan. (London : Hodder and Stoughton Educational, 1999)
This book is about: Foundation; Word processing; Spreadsheets; databases; painting and drawing; The Internet; and E-mail.
Keywords: Computer programs; Word processing; Microcomputers; Spreadsheets; Word processing; Microcomputers; Spreadsheets -- Computer programs; Computer software